Featured Answer

Asked on

I need help solving this problem....?

Solve equations by first removing parentheses and collecting like terms...solve equations with no solutions and equations with an infinite number of solutions.

solve.

2[ 5 - 3(4 - x ) ] - 7 = 3 [ 2 (5x - 1) + 8 ] -15

please show me how you work this type of problems.. thank you

Answers (2)

Collapse
dfr6ua91aa profile image
Collapse
djbbmmpuaa profile image

ok so first start off with 4-x which in turn will be 2[ 5 - 12 + 3x] - 7 = 3 [2 (5x-1) + 8] - 15. Next is taking care of the other parentheses and also combining like terms (the 12 and 5) 2[ -8 + 3x] - 7 = 3 [10x-2 + 8] - 15 Again common terms 2[ -8 + 3x] - 7 = 3 [10x + 6] - 15. Next is distributing which will be -16 + 6x - 7 = 30x + 18. Again Combine like terms -10x -7 = 30x + 18. Next you add the 10x over and subtract the 18 over which will get you -25 = 40x. Next is dividing (ughh) you will get 40/25 when reduced gets you 8/5 (8 over 5). so x = 8/5. Not sure if thats how it goes but thats what I got.